2015
DOI: 10.1016/j.energy.2015.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Managing the moisture content of wood biomass for the optimisation of Ireland's transport supply strategy to bioenergy markets and competing industries

Abstract: Publication information Energy, 86 : 354-368Publisher Elsevier Item record/more information http://hdl.handle.net/10197/7007 Publisher's statementThis is the author's version of a work that was accepted for publication in Energy. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publication. A definitive ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 36 publications
(50 reference statements)
2
10
0
Order By: Relevance
“…A fall in MC from 55% to 40% resulted in lower total transportation costs in all the biomass facility location scenarios analyzed. This confirms the results from previous studies, which have identified MC as one of the most important factors affecting the calorific value and transportation costs in biomass supply chains [49][50][51][52][53][54][55]. Thus, MC and transport distance constitute the factors with the major impacts on the biomass transportation efficiency from harvesting sites to biomass facilities [46,56].…”
Section: Biomass Supply Chain Costs In Tasmaniasupporting
confidence: 88%
“…A fall in MC from 55% to 40% resulted in lower total transportation costs in all the biomass facility location scenarios analyzed. This confirms the results from previous studies, which have identified MC as one of the most important factors affecting the calorific value and transportation costs in biomass supply chains [49][50][51][52][53][54][55]. Thus, MC and transport distance constitute the factors with the major impacts on the biomass transportation efficiency from harvesting sites to biomass facilities [46,56].…”
Section: Biomass Supply Chain Costs In Tasmaniasupporting
confidence: 88%
“…The constraints of topography and other factors are not considered. (7) There are no quantitative restrictions on the tools and equipment used for harvesting, processing, and transportation, and the efficiency of use has no effect on green job hours, economic costs, or CO 2 emissions. (8) The daily wages of labor in different supply links are consistent.…”
Section: Model Assumptionsmentioning
confidence: 99%
“…Some studies have focused on the optimization of the economic benefits of the raw material supply chain. Because economic benefits can be represented by the cost of the raw material supply chain [7][8][9], these optimization strategies primarily focus on supply chain costs. Specifically, Sara et al (2004) analyzed the raw material procurement costs, storage costs, storage losses, transportation costs, and other aspects to determine how to reduce the supply chain cost of the raw materials for forest biomass power generation [10].…”
mentioning
confidence: 99%
“…Raw biomass usually has low energetic density, which causes it to lose competitiveness with fossil fuels (Sosa et al, 2015). To reduce this characteristic, the thermochemical conversion of biomass can be a viable alternative.…”
Section: Introduction and Objectivesmentioning
confidence: 99%